2013
DOI: 10.7314/apjcp.2013.14.2.865
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Recommendations for an Effective Smoking Prevention Program for Indonesian Adolescents

Abstract: Background: The present qualitative study assessed the need, acceptability and appropriateness for implementing effective and culturally appropriate smoking prevention programs for adolescents in schools in Indonesia. Methods: Snowball sampling was used to recruit participants. The study sample comprised a mixture of staff in the education department, junior high school teachers and individuals who had taught junior high school students in Aceh Province, Indonesia. Data were collected through one hour in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This study was able to show improvements in knowledge between baseline and follow-up surveys for three SRH health topics and two smoking-related topics, including sensitive topics of medical abortions and condom use, which can to prevent unwanted pregnancies; these are rarely covered in existing SRH education programs in Indonesia. 39 We were also able to show improvements in knowledge about the harmful effects of both smoking and passive smoking, and promote the positive effects of quitting smoking. Overall, the study showed a significant increase in the mean knowledge score for both SRH and smoking components; and supportive evidence of potential intervention efficacy, with significant associations between increases in SRH knowledge and participants reporting 'that they learnt something new' from the SMS intervention: a promising result.…”
Section: Discussionmentioning
confidence: 83%
“…This study was able to show improvements in knowledge between baseline and follow-up surveys for three SRH health topics and two smoking-related topics, including sensitive topics of medical abortions and condom use, which can to prevent unwanted pregnancies; these are rarely covered in existing SRH education programs in Indonesia. 39 We were also able to show improvements in knowledge about the harmful effects of both smoking and passive smoking, and promote the positive effects of quitting smoking. Overall, the study showed a significant increase in the mean knowledge score for both SRH and smoking components; and supportive evidence of potential intervention efficacy, with significant associations between increases in SRH knowledge and participants reporting 'that they learnt something new' from the SMS intervention: a promising result.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, it is important to note that the present study involved Muslim adolescents only. While tobacco smoking is considered as age-inappropriate [ 13 ] and religiously forbidden behaviors for minors by the Indonesian Ulema Council [ 33 ], the benefits of tailoring school-based program interventions with participant’s religious background was also evidenced in this study. In fact, cultural sensitivity is an important factor for program effectiveness [ 34 ].…”
Section: Discussionmentioning
confidence: 84%
“…We also reviewed all available literature on religious based education programs, including those relating to smoking prevention and cessation, and synthesized these into what is called the Islam-based Intervention. Additionally, a qualitative research with teachers and policy makers in education from Aceh, Indonesia, was conducted in order to develop more culturally appropriate interventions and match with current curricula [ 13 ]. The programs employed both social influence and competence curricula.…”
Section: Methodsmentioning
confidence: 99%
“…There are multiple implications of this research for interventions to reduce the alcohol use of Muslim adolescents. It may be appropriate to incorporate substance use interventions in programs targeting religious youths and there is some evidence that this might be effective (Tahlil et al, 2013). The ability to accomplish this is facilitated by the religious homogeneity of Indonesian schools and the presence of religious instruction in the public and private school curricula.…”
Section: Discussionmentioning
confidence: 99%